Systematic Review of the Growth Rates and Influencing Factors in Thoracic Aortic Aneurysms. Issue 5 (May 2016) - Oladokun, D.; Patterson, B.O.; Sobocinski, J.; Karthikesalingam, A.; Loftus, I.; Thompson, M.M.; Holt, P.J.
Abstract : Objective/Background: The growth rates of thoracic aortic aneurysms (TAAs) and factors influencing their expansion are poorly understood. This study aimed to review systematically published literature describing TAA expansion and examine factors that may be associated with this. Methods: A comprehensive search of MEDLINE and Embase databases was performed until 30 April 2015. Studies describing rates of TAA growth were identified and systematically reviewed. Outcomes of interest were TAA growth rates and associated factors. Study quality was assessed using Scottish Intercollegiate Guidelines Network quality checklists for cohort studies. Results: Eleven publications, involving 1383 patients, met the eligibility criteria and were included in the review. Included studies were generally low in quality. Aneurysm measurement and growth-rate estimation techniques were inconsistently reported. Mean growth rates for all TAAs ranged from 0.2 to 4.2 mm/year. Mean growth rates for ascending and aortic arch aneurysms ranged from 0.2 to 2.8 mm/year, while those for descending and thoracoabdominal aneurysms ranged from 1.9 to 3.4 mm/year in studies reporting according to anatomical location. Large aneurysm size, distal aneurysm locations, presence of Marfan's syndrome, and bicuspid aortic valve were consistently associated with accelerated TAA growth. Presence of chronic dissection and chronic obstructive pulmonary disorder were also implicated as risk factors for faster TAA growth. Associations between medical comorbidity and aneurysm expansion were conflicting. Previous aortic surgery and anticoagulants were reported to have a protective effect on aneurysm growth in two studies. Conclusion: There is a shortfall in the understanding of TAA expansion rates. Existing studies are heterogeneous in methodology and reported outcomes. Identified unifying themes suggest that TAAs grow at a slow rate with large presenting diameter, distal aneurysm, and history of bicuspid aortic valve or Marfan's syndrome serving as main risk factors for accelerated aneurysm growth. High-quality studies with a standardised approach to TAA growth assessment are required.